Tubulocystic Carcinoma of the Bile Duct - Masahiro Takeuchi; Yoshitaka Sakamoto; Hirotsugu Noguchi; Sohsuke Yamada; Keiji Hirata (Case Reports in Hepatology)
Tubulocystic carcinoma of the bile duct is extremely rare and has not been reported in the literature. We reported a case of cystic neoplasm of the liver with distinct histopathological features that could not be clearly classified as of either mucinous or intraductal papillary neoplasm. A 68-year-old Japanese patient had a multicystic biliary tumor within the liver. This tumor was detected on follow-up of polymyalgia rheumatica. The exophytic, multicystic, 35 × 50 mm mass was composed of complex tubulocystic structures. We initially suspected cystadenocarcinoma of the liver and performed radical operation. However, pathology ultimately showed it to be very rare tubulocystic carcinoma that derived from the bile duct. We reviewed the literature and describe the process of our differential diagnosis.